2010
DOI: 10.1016/j.neuroscience.2010.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of mGluR8 receptors modulates retinal ganglion cell light responses

Abstract: Extracellular and whole-cell light-evoked responses of mouse retinal ganglion cells were recorded in the presence of the mGluR8 selective agonist, (S) . Off-light responses were reversibly reduced in the presence of DCPG in wild-type but not in mGluR8-deficient retinas. On-responses were only marginally modulated by DCPG. During Off-responses, DCPG suppressed both excitatory and inhibitory synaptic conductances suggesting that mGluR8 receptor activity reduces glutamate release from bipolar cell terminals and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The effects of 1 μM DCPG on the OFF excitatory current were significantly different from that of 10 μM AZ (p < 0.05) for both bright and dim stimuli, whereas the differing effect of these drugs on the outward currents approached statistical significance (p = 0.06). This reduction of the amplitude of the excitatory OFF response under DCPG is consistent with previous results (Awatramani and Slaughter, 2001; Higgs et al, 2002; Quraishi et al, 2010) further suggesting that mGluR8 is expressed within the direct OFF excitatory pathway for OFF ganglion cells.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The effects of 1 μM DCPG on the OFF excitatory current were significantly different from that of 10 μM AZ (p < 0.05) for both bright and dim stimuli, whereas the differing effect of these drugs on the outward currents approached statistical significance (p = 0.06). This reduction of the amplitude of the excitatory OFF response under DCPG is consistent with previous results (Awatramani and Slaughter, 2001; Higgs et al, 2002; Quraishi et al, 2010) further suggesting that mGluR8 is expressed within the direct OFF excitatory pathway for OFF ganglion cells.…”
Section: Resultssupporting
confidence: 93%
“…The effects of DCPG on the light responses of ganglion cells were consistent with our previous report of a decrease in spiking activity associated with OFF responses (Quraishi et al, 2010). Both ON and OFF excitatory currents in OFF-transient and ON-OFF-ganglion cells were reduced by DCPG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the mouse retina, it has been found that mGluR4, mGluR7, and mGluR8 are present in the inner plexiform layer (IPL), indicating their putative importance to inner retina processing (Quraishi et al,2007). A recent study has confirmed mGluR8 involvement in the modulation of ganglion cell electrophysiological responses to light stimulus (Quraishi et al,2010), but a study describing the effects of selective mGluR4, mGluR7, or mGluR8 activation or inhibition in retinal neurotransmitter release has never been conducted.…”
mentioning
confidence: 99%